The Radical Scavenging Activity and Thermal Stability of Cinnamon Extract-Loaded Nanoparticles - Dimas Rahadian Aji Muhammad; Joel Garcia Juvinal; Koen Dewettinck (Universitas Sebelas Maret, 2020)
The cinnamon extract-loaded nanoparticles with high phenolic content and antioxidant activity were successfully developed in a previous study. This study aimed to investigate the radical scavenging activity in 2.2-diphenyl-1-picrylhydrazyl system and stability of the nanoparticles under heat treatment. This study is important for directing the application of the nanoparticles in foods in the future. The thermal stability test was conducted using two different methods, which were the combination of relatively lower temperature (20-100°C) with a long time treatment (up to 120 hours) and the combination of relatively higher temperature (110-150°C) with a short time treatment (equal to or less than 2 hours). The results show that the cinnamon extract-loaded nanoparticles exhibited a radical scavenging activity. The higher proportion of cinnamon loading resulted in the higher radical scavenging activity of the nanoparticles. The thermal treatment caused a significant degradation on the phenolic content and antioxidant activity of the nanoparticles. The energy activation (Ea) of the phenolic content and antioxidant activity was found at 35.17 kJ mol-1 and 27.91 kJ mol-1, respectively. This study suggests that the cinnamon extract-loaded nanoparticles might be preferably incorporated into foods minimally involving heat exposure during their manufacture.